Investigating the influence of infill percentage on the mechanical properties of fused deposition modelled ABS parts (2016)
3D printing is a manufacturing process that is usually used for modeling and prototyping. One of the most popular printing techniques is fused deposition modeling (FDM), which is based on adding melted material layer by layer. Although FDM has several advantages with respect to other manufacturing materials, there are several problems that have to be faced. When setting the printing options, several parameters have to be taken into account, such as temperature, speed, infill percentage, etc. Selecting these parameters is often a great challenge for the user, and is generally solved by experience without considering the influence of variations in the parameters on the mechanical properties of the printed parts.This article analyzes the influence of the infill percentage on the mechanical properties of ABS (Acrylonitrile Butadiene Styrene) printed parts. In order to characterize this influence, test specimens for tensile strength and Charpy tests were printed with a Makerbot Replicator 2X printer, in which the infill percentage was varied but the rest of the printing parameters were kept constant. Three different results were analyzed for these tests: tensile strength, impact resistance, and effective printing time. Results showed that the maximum tensile force (1438N) and tensile stress (34,57MPa) were obtained by using 100% infill. The maximum impact resistance, 1,55J, was also obtained with 100% infill. In terms of effective printing time, results showed that printing with an infill range between 50% and 98% is not recommended, since the effective printing time is higher than with a 100% infill and the tensile strength and impact resistance are smaller. In addition, in comparing the results of our analysis with results from other authors, it can be concluded that the printer type and plastic roll significantly influence the mechanical properties of ABS parts.